2005
DOI: 10.3892/ijo.26.5.1217
|View full text |Cite
|
Sign up to set email alerts
|

Methylation and expression of p16INK4 tumor suppressor gene in primary colorectal cancer tissues

Abstract: It is known that p16 INK4 tumor suppressor gene expression in colon cancer cells is repressed by methylation at the CpG island of promoter, but in vivo silencing of p16 gene is not fully understood. Some studies showed that primary colorectal cancer (CRC) tissues often overexpress the p16 protein, while others showed the high incidence of p16 methylation. The aim of this study was to clarify p16 gene regulation in vivo. We used real-time methylationspecific PCR (MSP) to examine density of p16 methylation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
23
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
5
23
1
1
Order By: Relevance
“…Methylation was seen in 33% of the whole series and it was, like K-Ras mutation, significantly associated with a M þ phenotype (univariate analysis P ¼ 0.011; multivariate analysis P ¼ 0.001). A strong correlation between staging and p16INK4A methylation was found also by Yi et al (2001); loss of p16INK4A expression has been previously associated with lymph-node metastases (Kim et al, 2005a) and more advanced stage (Jeong et al, 2005). Altogether, these results suggest that p16INK4A methylation might link to a more malignant phenotype in CRC; interestingly Liang et al (1999) recently reported an association between p16INK4A methylation and shorter survival of CRC.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Methylation was seen in 33% of the whole series and it was, like K-Ras mutation, significantly associated with a M þ phenotype (univariate analysis P ¼ 0.011; multivariate analysis P ¼ 0.001). A strong correlation between staging and p16INK4A methylation was found also by Yi et al (2001); loss of p16INK4A expression has been previously associated with lymph-node metastases (Kim et al, 2005a) and more advanced stage (Jeong et al, 2005). Altogether, these results suggest that p16INK4A methylation might link to a more malignant phenotype in CRC; interestingly Liang et al (1999) recently reported an association between p16INK4A methylation and shorter survival of CRC.…”
Section: Discussionsupporting
confidence: 58%
“…The p16INK4A product, an inhibitor of cyclin-dependent kinases 4 and 6, is capable of preventing Rb phosphorylation, thus blocking cells in the G1 phase of the cell cycle (Serrano et al, 1996). It is known that p16INK4A expression in colon cancer cells is repressed by methylation at the CpG island of promoter, but in vivo silencing of p16INK4A methylation has not been widely investigated (Kim et al, 2005a).…”
mentioning
confidence: 99%
“…Correlations with various clinico-pathological parameters, such as grading (40), lymph node metastasis (41,42) and prognosis (40,42,43), remain unconfirmed by others (24,36,43). Our study and those of other authors (24,31,36,42,43) could not reveal a clinico-pathological relevance of the tumor suppressor gene.…”
Section: Discussioncontrasting
confidence: 52%
“…However, the cytoplasmic expression of the cell cycle regulator was observed to be reduced at advanced pN stages. Analogously, Kim et al (41) demonstrated that decreased p16 expression was associated with lymph node metastasis and increased tumor size, while increased expression correlated with a low incidence of metastasis. Furthermore, Tada et al (42) revealed that the average rate of lymph node metastases was significantly higher in tumors exhibiting low levels of the tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 73%
“…In the present study, we were supposed to find out if most of the gastrointestinal cancer patients have methylated p16 promoter because there are many researches which support this idea and our findings also correlate with other researches. Kim et al (29) suggested that methylation of p16 causes low expression level of p16 and that situation may contribute to tumor enlargement. According to the clinicopathological analysis, p16 metyhlation in serum of the patients with colorectal cancer was related with later Dukes' stage (17).…”
Section: Discussionmentioning
confidence: 99%